In vitro antimicrobial effects of Myristica fragrans essential oil on foodborne pathogens and its influence on beef quality during refrigerated storage. Issue 3 (3rd March 2020) - Kiarsi, Zahra; Hojjati, Mohammad; Behbahani, Behrooz Alizadeh; Noshad, Mohammad
Abstract: Nutmeg ( Myristica fragrans ) seed was subjected to the hydro‐distillation method to extract its essential oil (NEO). Its main constituents were α‐pinene (20.16%), sabinene (14.45%), and β‐pinene (13.26%) with great antimicrobial and antioxidant actions. A novel edible coating was then fabricated based on the sage seed mucilage (SSM) and NEO, to ameliorate the quality and shelf‐life of beef slices. The NEO‐loaded SSM coating was able to significantly decrease the population of total viable count, Escherichia coli, Staphylococcus aureus, psychrotrophic bacteria, and fungi. Moreover, lipid oxidation of beef slices was remarkably suppressed upon the application of bioactive NEO‐loaded SSM edible coating, as compared with the control by Day 6. The coated beef sample, especially NEO‐rich SSM coated ones perceived a higher consumer acceptance and firmness than the SSM coated and noncoated samples. The SSM edible coating containing NEO could therefore have the potential to control the growth of pathogenic microorganisms and lipid oxidation, and to improve the color stability and sensory properties of meat and meat products. Abstract : The use of nutmeg essential oil‐loaded sage seed mucilage‐based coating with oxygen barrier effect along with antioxidant and antimicrobial activity enhanced the beef shelf‐life by lowering the moisture losses, microbial growth rate, and oxidation reaction progression, as well as by improving the sensory properties of the product. Therefore, the nutmeg essential loaded edible coating with outstanding antimicrobial and antioxidative property could be applied as a novel food‐born preservative to amend the shelf‐life of various food products.